Dreidimensional bildgebendes Radarsystem mit digitaler Strahlformung für industrielle Anwendungen - Harter, Marlene (Karlsruher Forschungsberichte aus dem Institut für Hochfrequenztechnik und Elektronik, 2014)
The contactless detection of the presence and position of objects is required in many areas of the industry. Therefore, a three-dimensional measuring radar sensor, including corresponding methods for signal processing, is designed and realized. By exemplary measurement scenarios, the capability of the radar system for positioning and imaging of the environment in three dimensions is successfully demonstrated, which opens up new areas of application.